Uso de álcool e problemas relacionados no povo indígena Maxakali/MG: a visão de mundo maxakali - Roberto Carlos de Oliveira (2018)
Alcohol use and alcohol related problems among Maxakali Indigenous Peoples/MG: A Maxakali world view Through an exploratory sequential design, a comprehensive phenomenological approach was conduct with the purpose to understand the social perceptions regarding the alcohol use and their related problems among Maxakali Indigenous Peoples/MG/Brazil. It started from the realities lived by the research subjects narrated in seven focus group. Through thematic analysis, the results of the qualitative research were organized into themes and three dimensions: pattern of consumption (initiation, frequency, quantity); contexts (access, where, how, when and who) and related problems (individual, family and villages). We present these arguments and explore how the findings were developed in constructions and questions of the questionnaire. Followed by a quantitative study we explore the collectivist characteristic of the Maxakali culture. We developed and applied a questionnaire with Maxakali leaderships who answered about their friends alcohol consumption in last year, also the alcohol related problems. The association between alcohol consumption and consequences with sociodemographic data of the interviewees was analyzed using chi-square and Fisher's exact tests and Cluster Analysis. The Kappa values were calculated to evaluate the reproducibility of the questionnaire. The qualitative findings highlighted that, with the emergence of the Kaxmuk-related ethylic regime, there were adaptations with negative relations for the drinker, his family, his village and his community. It recognized the ways in which the native drinks have disappeared, and the liquor has inserted itself into their cultural systems. Considering the subjectivity of those leaders in the process of data collection and analysis, functions regarding social lubricant, facilitator of shamanic trances, knowledge production and its role in the relations of gender and age were identified. Those functions were enmeshed to their symbols and meanings regarding to their drinking pattern and contexts. In the world-of-life, these changes can be seen through accidents, insults, marital disharmony, neglects, violent behavior, illness and death. The quantitative results point out that, the prevalence of 12 months of alcohol use was 39.1%. The alcohol use rate to women (17.3%) was 3.6 times lower than the men's rate. For males, alcohol rates increased from 8.1% to 64% in the age group from 09 to 14 to 15 to 19 years-old. The highest proportions of alcohol use among parents were found in extended families and associated with the negative consequences of those who use cachaça. On the other hand, the nuclear families had an association of protection to the use of alcohol in the age group of 9 to 14 years in the female gender. In spite of the use of alcohol in the female beginning from 20 to 24 years, the rates of problems related to this use by the women surpassed those of men during the 25 to 45 years of age. With a substantial agreement of reproducibility in the application of the questionnaire, our hope is that the ease of application and the predictive force of this tool will allow the detection and monitoring of alcohol use and its consequences in the Maxakali people. Keywords: South american Indians. Alcoholic beerages. Alcohol, use. Social problems. Qualitative research. Quantitative research